Rencana Strategis Dan Rencana Operasional Dalam Lembaga Pendidikan Islam - Eri Samsidar; Ahmad Nazir (UIN Fatmawati Sukarno Bengkulu, 2021)
Abstract: Strategic plans are still weak in managing current conditions and projected future conditions, such as long-term or medium-term planning in determining strategic goals and objectives, and operational plans are still weak at the human resource level. Using descriptive qualitative method. The purpose of this paper is to map and analyze strategic plans and operational plans in Islamic educational institutions. The results show; First, the strategic plan as an important policy as the basis for making institutional programs in formulating vision, mission and goals by involving stakeholders. Strategic plan as a systematic and formal effort of an institution to clarify the main objectives, policies and strategies. Second, the operational plan as the implementation of the program to achieve the vision, mission and goals in the form of concrete steps in the operation of an Islamic educational institution, and Third, the relationship between the strategic plan and the operational plan is an integral part and cannot be separated in the development of educational institutions. The author can suggest in this paper to involve the perspective of leadership and management elements by accommodating the experiences and problems encountered in managing strategic plans and operational plans in Islamic educational institutions, so that a comprehensive solution can be found.Keywords: Strategic Plan, Operational Plan, Islamic Educational Institution. Abstrak: Rencana strategis masih lemah dalam mengelola kondisi saat ini dan proyeksi kondisi masa depan, seperti perencanaan jangka panjang atau jangka menengah dalam menentukan tujuan dan sasaran strategis, dan rencana operasional masih lemah pada tingkat sumberdaya manusia. Menggunakan metode kualitatif deskriptif. Tujuan tulisan ini memetakan dan menganalisis rencana strategis dan rencana operasional dalam lembaga pendidikan Islam. Hasilnya menunjukkan; Pertama, rencana strategis sebagai kebijakan penting sebagai dasar dalam membuat program kelembagaan dalam merumuskan visi, misi dan tujuan dengan melibatkan stakeholders. Rencana strategis sebagai usaha sistematis dan formal suatu lembaga untuk memperjelas sasaran utama, kebijakan-kebijakan dan strategi. Kedua, Rencana operasional sebagai penerapan program pencapaian visi, misi dan tujuan berupa langkah nyata dalam pengoperasionalan sebuah lembaga pendidikan Islam, dan Ketiga, Hubungan rencana strategis dengan rencana operasional merupakan satu kesatuan dan tidak dapat dipisahkan dalam pengembangan lembaga pendidikan. Penulis dapat menyarankan dalam penulisan ini untuk melibat perspektif unsur kepemimpinan dan pengelola dengan mengakomodasi pengalaman dan masalah yang dihadapi dalam mengelola rencana strategis dan rencana operasional dalam lembaga pendidikan Islam, sehingga solusi yang menyeluruh dapat ditemukan. Kata Kunci: Rencana Strategis, Rencana Operasional, Lembaga Pendidikan Islam.